Nutritional dermatoses and its association with anemia and systemic illness - Lakhani, Som J.; Surti, Nishit K.; Doshi, Mrugal V.; Panchasera, Sanket R.; Vasvani, Vivek N.; Bapna, Mani R.; Raval, Ranjan C.; Billimoria, Freny E.; Lakhani, Jitendra D. (International Journal of Research in Dermatology, 2018)
Background: Mucocutaneous changes may be a “tell-tale” signs of multi nutrional deficiency including anemia. Some are very characteristic of a specific nutrient deficiency, while other signs may overlap and will reflect multiple deficiency states. Methods: To scrutinize clinical signs of multi nutritional deficiencies accompanied with anemia, this observational clinical study of 75 patients (adult and adolescents) was undertaken. Patients were selected from out-patient and in-patient department (OPD and IPD) of dermatology as well as General Medicine ward including medical ICU. Relevant investigations were carried out whenever required. Detail clinical history of diet, tuberculosis as well as HIV disease, worm infestation, other co-morbid conditions and alcohol intake were taken. Clinical signs of nutritional deficiencies like of Pellagra, Kwashiorkor, Beriberi, Ariboflavinosis and other signs of avitaminosis and micronutrient deficiency were looked for in all such patients. Results: Of 75 patients, 37 were male (M) and 38 female (F). One of the important findings was that one third patients were admitted in ICU and in 60 of 75 patients risk factors could be identified. Mental illness, ICU admission, elderly age, systemic illness and alcohol consumption were the predisposing factors. Iron deficiency anemia was the commonest anemia followed by dimorphic anemia with other multinutrional manifestations. Clinical signs which were observed due to multinutritional deficiency were of pellagra dermatosis, kwashiorkor, koilonychia with pale tongue and mucous membranes, angular cheilosis, hair changes of various types and other signs due to systemic involvement. Conclusions: Anemia may be associated with other nutritional abnormality which is reflected in changes in the skin, mucous membrane, hairs and nails. Nutritional dermatosis and anemia can be part of systemic illness which maybe reflected as deficiency of multiple nutritive factors.